ORGANIZACIÓN DE LA CONTABILIDAD EN EL ALMACÉN AGROPECUARIO “LA CASA DEL AGRICULTOR” DE LA CIUDAD DE LOJA. PERIODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2017 - Piedra Guaycha, Wendy Juleicy (2019)
The development of the thesis present, denominated "ORGANIZATION OF THE ACCOUNTING IN THE AGRICULTURAL WAREHOUSE "THE HOUSE OF THE FARMER" OF THE CITY DE LOJA. PERIOD OF SEPTEMBER 01 AT DECEMBER 31 THE 2017", it made it to him with the purpose of organizing a countable process in order to know real data through the financial states, contributing this way to the taking of opportune decisions for the development and growth of the company. To implement the accounting in the agricultural warehouse "La Casa del Agricultor", an adequate accounting process and record was carried out based on the support documents, starting with the determination of the initial inventory, observing the assets, values and obligations of the company; based on the collection of information from the source documents, the design of purchasing, sales, accounts receivable and payable assistants was made, which facilitated the proper registration of transactions; A plan and manual of accounts was established according to the policies, objectives and needs of the warehouse; the accounting process was developed obtaining with it the financial statements, in which the results of the economic operations are demonstrated, besides indicators were applied, to measure the financial structure of the company. The results obtained from the accounting process carried out at the agricultural warehouse "La Casa del Agricultor", allowed to know through the financial statements the net profit of $ 1,410.59, the capital of $ 161,350.11, the total assets of $ 269,673.09, its liabilities of $ 106,083.95, which indicates that the company has solvency to cover its obligations, being important to highlight that the assets in 39% are financed with debt or held by third parties.